2021
DOI: 10.1002/batt.202000258
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Nature of Solid‐Electrolyte Interphase on Lithium Metal in Liquid Electrolytes: A Review on Growth, Properties, and Application‐Related Challenges

Abstract: A stable solid‐electrolyte interphase (SEI) is of crucial essence for realization of lithium (Li) metal batteries. This article provides an overview of attempts undertaken to understand the nature of the natural SEI, including growth behavior at the open circuit potential and under cycling conditions as well as underlying causes of instabilities. Additionally, the influence of features such as morphology and composition of the SEI and electrolyte properties on the charge transport and transfer mechanism, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 111 publications
0
14
0
Order By: Relevance
“…On one hand, SEI formation requires the decomposition of various electrolyte components, a robust SEI once formed restricts further direct contact between the electrode and electrolyte thereby obstructing further electrolyte decomposition which can positively contribute to the longevity of the battery . In various reports, it has been proposed that an inorganic-rich SEI layer is recommended as it is robust and stops dendrite formation. , The organic rich SEI on the other hand leads to low ionic conductivity in the battery . Among the considered salts (LiPF 6 , LiBF 4 , and LiTFSI) in our study, LiBF 4 is found to have the least tendency to participate in SEI formation.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…On one hand, SEI formation requires the decomposition of various electrolyte components, a robust SEI once formed restricts further direct contact between the electrode and electrolyte thereby obstructing further electrolyte decomposition which can positively contribute to the longevity of the battery . In various reports, it has been proposed that an inorganic-rich SEI layer is recommended as it is robust and stops dendrite formation. , The organic rich SEI on the other hand leads to low ionic conductivity in the battery . Among the considered salts (LiPF 6 , LiBF 4 , and LiTFSI) in our study, LiBF 4 is found to have the least tendency to participate in SEI formation.…”
Section: Resultsmentioning
confidence: 88%
“…14 In various reports, it has been proposed that an inorganic-rich SEI layer is recommended as it is robust and stops dendrite formation. 46,47 The organic rich SEI on the other hand leads to low ionic conductivity in the battery. 21 Among the considered salts (LiPF 6 , LiBF 4 , and LiTFSI) in our study, LiBF 4 is found to have the least tendency to participate in SEI formation.…”
Section: M Litfsi In Ecmentioning
confidence: 99%
“…[12][13][14] The experimental difficulties of SEI studies include air-sensitivity and the inherently complex and fragile SEI morphology composed of many chemical compounds with variable mechanical properties and sometimes non-negligible amount of pores. [15][16][17][18][19][20][21][22][23] The above mentioned problems pose even greater challenges for the studies of SEIs on the reactive Li/Na metals, currently considered to be the attractive anode materials for future-generation batteries. [24][25][26][27][28] Although novel experimental strategies such as cryo-transmission electron microscopy (TEM), [29][30][31][32] X-ray-based analytical tools [33][34][35] and nuclear magnetic resonance (NMR) spectroscopy have been recently applied in SEI research, 32,[36][37][38][39][40] EIS offers particular advantages, as it enables us to distinguish between different electrochemical transport processes in situ and in a non-destructive way.…”
Section: Introductionmentioning
confidence: 99%
“…The SEI generated in traditional carbonate electrolytes is composed primarily of Li 2 CO 3 , Li 2 O, and Li alky carbonate (mosaic model, Figure 1e). [12,15,17,32] These components would not satisfy the demand of homogeneity, rapid ion transport, and mechanical strength (Figure 1f), which are needed to achieve high reversibility of Li metal anode [29,33–35] . Recent studies have shown that many inorganic molecules (LiF, Li 3 N, Li 2 S, etc.)…”
Section: Introductionmentioning
confidence: 99%